Clinical Decision Analysis - Taylor, Th. R. (Methods of Information in Medicine, 1976)
Attempts have been made for almost two decades to use computers to make clinical diagnoses. Interest in such techniques persists despite little practical success in their application to routine patient care. The explanation of this lack of success is complex and includes (i) lack of understanding of the decisionmaking process itself and (ii) the need for a theoretical framework within which such systems can be developed. A major objective of this paper is to illustrate the contribution that the concepts and techniques associated with Decision Theory can make to both of these problems.After attempting to analyse the deficiencies of current approaches to computer-assisted diagnosis the paper discusses some of the basic concepts of decision theory. It then illustrates the role of decision theory in studies using different forms of clinical decision analysis.Finally the paper indicates the relevance of decision analysis to medical education and to the provision of health care.
Keywords: Decision Analysis; Computer-assisted Diagnosis; Medical Education; Health Care